2005
DOI: 10.1096/fj.05-3778fje
|View full text |Cite
|
Sign up to set email alerts
|

Key gravity‐sensitive signaling pathways drive T‐cell activation

Abstract: Returning astronauts have experienced altered immune function and increased vulnerability to infection during spaceflights dating back to Apollo and Skylab. Lack of immune response in microgravity occurs at the cellular level. We analyzed differential gene expression to find gravity-dependent genes and pathways. We found inhibited induction of 91 genes in the simulated freefall environment of the random positioning machine. Altered induction of 10 genes regulated by key signaling pathways was verified using re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
142
1
5

Year Published

2006
2006
2012
2012

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 147 publications
(163 citation statements)
references
References 42 publications
(58 reference statements)
15
142
1
5
Order By: Relevance
“…For this study they used Human Genome Focus Arrays (Affymetrix) and identified 91 down-regulated genes as a result of exposure to simulated microgravity. The expression of early genes regulated primarily by transcription factors NF-κB, CREB, ELK, AP-1, and STAT were impaired in microgravity, suggesting that microgravity either slows, impedes, or fully blocks key signaling pathways in early T cell activation (Boonyaratanakornkit et al, 2005). They showed that IL-2 was among the down-regulated genes, which correlates well with previous nonarray based reports (Cogoli et al, 1993;Pippia et al, 1996;Walther et al, 1998;HughesFulford et al, 2005).…”
Section: Microarray Analysis Of Microgravity Exposed Cells Of the Immsupporting
confidence: 85%
“…For this study they used Human Genome Focus Arrays (Affymetrix) and identified 91 down-regulated genes as a result of exposure to simulated microgravity. The expression of early genes regulated primarily by transcription factors NF-κB, CREB, ELK, AP-1, and STAT were impaired in microgravity, suggesting that microgravity either slows, impedes, or fully blocks key signaling pathways in early T cell activation (Boonyaratanakornkit et al, 2005). They showed that IL-2 was among the down-regulated genes, which correlates well with previous nonarray based reports (Cogoli et al, 1993;Pippia et al, 1996;Walther et al, 1998;HughesFulford et al, 2005).…”
Section: Microarray Analysis Of Microgravity Exposed Cells Of the Immsupporting
confidence: 85%
“…The RPM was operated as a random walk three-dimensional clinostat (basic mode) with an angular velocity of rotation of 60 deg s À1 (Walther et al, 1998) for 10 days (maximum cultivation time allowance for that facility). Random rotation at 60 deg s À1 , 1-10 cm away from the center of rotation, yields gravity contours from 1.12 Â 10 À3 to 1.12 Â 10 À2 g as calculated by g 0 ¼ (o 2 R)/g 0 , where o ¼ 1.05 radian s À1 , R ¼ 0.01-0.10 m and g 0 ¼ 9.81 m s À2 (Hoson et al, 1997;Boonyaratanakornkit et al, 2005).…”
Section: Methodsmentioning
confidence: 99%
“…Weightlessness may also contribute to flight-associated immune dysregulation. In-flight and ground-based studies have shown that the lack of gravity impedes signalling pathways essential for early T-cell activation 50 and leads to alterations in the organization of the cytoskeleton and microtubule organizing centres. 51,52 Potential adverse clinical events that may be related to prolonged dysregulation of the immune system include hypersensitivities, autoimmunity, allergies, infectious diseases, latent viral reactivation and even malignant diseases.…”
Section: Immune Dysregulationmentioning
confidence: 99%